2016
DOI: 10.3949/ccjm.83.s1.04
|View full text |Cite
|
Sign up to set email alerts
|

Newer oral and noninsulin therapies to treat type 2 diabetes mellitus

Abstract: The pathophysiology of type 2 diabetes mellitus involves several biologic mechanisms and no single medication addresses them all. Most patients require more than one medication to adequately treat their diabetes, needing drugs with unique and complementary mechanisms of action to address and balance insulin and glucagon levels. In the past decade, several therapeutic drug classes have been developed for type 2 diabetes mellitus. Each provides therapeutic options with novel mechanisms of action to help clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…[7][8][9] GLP-1RAs have glucose-dependent antidiabetic effects, and the risk of hypoglycaemia is comparatively low. [10][11][12] They also inhibit glucagon secretion from pancreatic α cells, thereby inhibiting abnormal hepatic glycogen output. [10][11][12] GLP-1RAs reduce gastrointestinal motility and inhibit central appetite, thereby reducing food intake and body weight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] GLP-1RAs have glucose-dependent antidiabetic effects, and the risk of hypoglycaemia is comparatively low. [10][11][12] They also inhibit glucagon secretion from pancreatic α cells, thereby inhibiting abnormal hepatic glycogen output. [10][11][12] GLP-1RAs reduce gastrointestinal motility and inhibit central appetite, thereby reducing food intake and body weight.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] They also inhibit glucagon secretion from pancreatic α cells, thereby inhibiting abnormal hepatic glycogen output. [10][11][12] GLP-1RAs reduce gastrointestinal motility and inhibit central appetite, thereby reducing food intake and body weight. [10][11][12] Furthermore, animal experiments showed that GLP-1 promotes the proliferation of pancreatic β cells and inhibits β cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, nearly 50% of patients with type 2 diabetes (T2D) are living with uncontrolled hyperglycemia [1,2], despite the introduction of numerous new diabetes medications over the past two decades [3,4]. A retrospective analysis of US claims data from 1.66 million patients with T2D showed a declining trend (from 56.4% in 2006 to 54.2% in 2013; p \ 0.001) in patients achieving a glycated hemoglobin (HbA1c) target of \ 7.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the previously used oral antihyperglycemic drugs are still as important, newer drugs will in the future replace metformin and sulfonylurea. In this new era of 2018, we are focusing on new add-on oral hypoglycemic drugs which could possibly be adopted by the population of patients with T2DM [ 1 ].…”
Section: Introductionmentioning
confidence: 99%